(untitled) (Research, Society and Development, 2022)
Innovation has a strong growth trend in the financial market and one of those impacted in this scenario is the customer. Many services that were only performed in person at physical branches and with the intervention of an employee, can now be performed via apps, internet banking platforms and self-service terminals. All this technological revolution has brought many benefits to the population, however, not everyone is open to changing the culture of using the services provided by financial institutions. Therefore, this review aims to analyze and qualify publications on the impact of innovation on consumer behavior in financial institutions. Therefore, a systematic literature review (RSL) was carried out based on the question that guided the study. Searches were carried out in the Scopus database, resulting in 24 articles that were used for analysis. As for the technique, the bibliometric study and content analysis will be applied. The results present several characteristics and indicators related to the analyzed publications.